Registration of Trademarks Rejected in Other Countries in Accordance with Ratification of the Madrid Protocol: Pendaftaran Merek Yang Ditolak di Negara Lain Sesuai Dengan Ratifikasi dari Protokol Madrid - Sasvia, Hayyu; Sulistianingsih, Dewi (Faculty of Law, Universitas Negeri Semarang, 2024)
Current globalization has had an impact on goods, services, labor, etc. that flow freely between countries in the world. Indonesia itself is no exception to this global phenomenon. The free flow of trade in and out of Indonesia makes products from Indonesia vulnerable to being imitated if they are not protected, especially protecting their trademarks. Not only brands from Indonesia must be protected domestically, but they also need protection abroad. Efforts to protect brands from Indonesia can be carried out through country or international registration mechanisms. This article attempts to explain that international registration can be carried out effectively through the Madrid Protocol, which provides for centralized trademark registration at the World Intellectual Property Organization (WIPO), rather than registering trademarks centrally. Trademarks in the respective countries where the goods or services are intended to be traded. The purpose of this article is to find out how the implementation of trademark registration based on the Madrid Protocol after its ratification in Indonesia and how the impact of trademark registration carried out in Indonesia has had an impact in other countries that have implemented and ratified this system.